Between Algorithm and Model: Different Molecular Surface Definitions for the Poisson-Boltzmann Based Electrostatic Characterization of Biomolecules in Solution (Communications in Computational Physics, 2013)
The definition of a molecular surface which is physically sound and computationally efficient is a very interesting and long standing problem in the implicit solvent continuum modeling of biomolecular systems as well as in the molecular graphicsfield. In this work, two molecular surfaces are evaluated with respect to their suitability for electrostatic computation as alternatives to the widely used Connolly-Richardssurface: the blobby surface, an implicit Gaussian atom centered surface, and the skinsurface. As figures of merit, we considered surface differentiability and surface areacontinuity with respect to atom positions, and the agreement with explicit solvent simulations. Geometric analysis seems to privilege the skin to the blobby surface, andpoints to an unexpected relationship between the non connectedness of the surface,caused by interstices in the solute volume, and the surface area dependence on atomiccenters. In order to assess the ability to reproduce explicit solvent results, specificsoftware tools have been developed to enable the use of the skin surface in Poisson-Boltzmann calculations with the DelPhi solver. The results indicate that the skin andConnolly surfaces have a comparable performance from this last point of view.